2016
DOI: 10.1542/peds.2015-3967
|View full text |Cite
|
Sign up to set email alerts
|

A Core Outcome Set for Children With Feeding Tubes and Neurologic Impairment: A Systematic Review

Abstract: CONTEXT: Uncertainty exists about the impacts of feeding tubes on neurologically impaired children. Core outcome sets (COS) standardize outcome selection, definition, measurement, and reporting. OBJECTIVE:To synthesize an evidence base of qualitative data on all outcomes selected and/ or reported for neurologically impaired children 0 to 18 years living with gastrostomy/ gastrojejunostomy tubes. DATA EXTRACTION: Outcomes were extracted and assigned to modified Outcome Measures in Rheumatology 2.0 Filter core a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 125 publications
4
44
0
1
Order By: Relevance
“…[1][2][3] Though gastrostomy and gastrojejunostomy tubes have been shown to improve nutritional outcomes in this population, there is uncertainty regarding their impact on survival, respiratory health, healthcare utilization and cost, feeding times, caregiving burden, and child and primary caregiver quality of life. 9 The results were similar to the findings of outcome reporting across studies in other childhood diseases that includes substantial heterogeneity in the outcomes selected for measurement, absent or inadequate reporting of outcome definitions, and limited reporting of the rationale for outcome selection. 9 We found that studies most often reported clinical and physiological indicators of health associated with gastrostomy/ gastrojejunostomy tube interventions, while patient/parent-reported outcomes and resource use were less often measured.…”
supporting
confidence: 76%
See 2 more Smart Citations
“…[1][2][3] Though gastrostomy and gastrojejunostomy tubes have been shown to improve nutritional outcomes in this population, there is uncertainty regarding their impact on survival, respiratory health, healthcare utilization and cost, feeding times, caregiving burden, and child and primary caregiver quality of life. 9 The results were similar to the findings of outcome reporting across studies in other childhood diseases that includes substantial heterogeneity in the outcomes selected for measurement, absent or inadequate reporting of outcome definitions, and limited reporting of the rationale for outcome selection. 9 We found that studies most often reported clinical and physiological indicators of health associated with gastrostomy/ gastrojejunostomy tube interventions, while patient/parent-reported outcomes and resource use were less often measured.…”
supporting
confidence: 76%
“…6 Gastrostomy and gastrojejunostomy tubes are placed to address these challenges. 9 We found that studies most often reported clinical and physiological indicators of health associated with gastrostomy/ gastrojejunostomy tube interventions, while patient/parent-reported outcomes and resource use were less often measured. 5,7,8 In a recent systematic review of studies in children with neurological impairment and gastrostomy/gastrojejunostomy tube dependence, we summarized all reported health outcomes measured after tube insertion.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Although the estimation of FM with skinfolds has limitations and underestimation 32 , it is useful for follow-up, especially when weight and height are difficult to measure, as in the prostrate and/or column deformities. This is important, because despite being weakened, the FM of CP patients may be similar to normal, by proportional decrease of body weight components 39 . The main cause of morbidity and mortality were respiratory infections in our study, according to what was published 4,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Taken in a timely manner, the insertion of a GT improves nutritional status and fat mass, decreases respiratory infections and hospitalizations in patients with CP 35,36 . However, patient heterogeneity and measurements, coupled with inadequate design studies make it difficult to demonstrate its benefits [37][38][39] . Moreover, it has been shown that survival at age 19 is greater in those without WG (72% versus 55%) 27 , but this study suggests that the association between WG use and morbidity and mortality should be investigated prospectively , Considering the patient's condition at the time of the WG, in order to evaluate if the greatest risk is real or if it is only about patients with greater fragility and vital risk 5 .…”
Section: Discussionmentioning
confidence: 99%